PENGARUH PENGGUNAAN TEPUNG TULANG IKAN SWANGGI (Priacanthus tayenus) TERHADAP KUALITAS MUTU FISIK DAN PROKSIMAT PAKAN IKAN - Sikumbang, Mohammad Nuril Akbar; Soeprijadi, Liliek; Rachma, Sasya Karina; Mukhaimin, Iman (Politeknik Kelautan dan Perikanan Bitung, 2023)
The objective of this research is to determine the optimal formulation for fish feed production by utilizing by-products from the swanggi fish (Priacanthus tayenus) surimi process, corn cob flour, and fine bran, considering parameters such as hardness, durability, buoyancy, load resistance, water resistance, buoyancy time, sensory evaluation, and proximate analysis. The study is divided into several stages, namely the production of swanggi fish bone meal, corn cob flour production, and fish feed production using four different formulations based on varying amounts of swanggi fish bone meal: F1 (400 grams), F2 (450 grams), F3 (500 grams), and F4 (550 grams). Quality testing of fish feed includes physical tests for hardness, durability, buoyancy, sensory evaluation, and proximate analysis. Fish feed has been successfully produced using four different formulations, with the best formulation determined through sensory analysis and physical tests, particularly formulation F1. The average value for F1 in terms of shape, odor, and texture parameters is 3.88. The best physical test results for the fish feed product are observed in formulation F1, with hardness not breaking under a 500-gram load, underwater durability lasting for 70 minutes before sinking, and buoyancy lasting for 62 minutes until the feed sinks. The highest proximate content is found in formulation F4, which complies with the SNI 01-7242-2006 standard for tilapia fish feed for rearing and growth, with protein content at 30.29%, fat content at 40.36%, moisture content at 5.25%, ash content at 7.85%, and carbohydrate content at 16.25%.